1983
DOI: 10.1159/000249754
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Keloids with Excision and Postoperative X-Ray Irradiation

Abstract: During a 9-year period 47 patients with 62 keloids, treated with excision and postoperative superficial X-ray irradiation, were included in a retrospective study. The follow-up time was 6 months to 9 years. 88% experienced a good or excellent result. Single or fractioned dose and time interval between excision and radiation did not influence the result. Hyperpigmentation was noted as a side effect in 16 of 47 patients. More favorable results were obtained in the treatment of small keloids and of keloids locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 3 publications
(5 reference statements)
1
39
0
1
Order By: Relevance
“…Therefore, early intervention with radiotherapy should be the best timing for the treatment of keloids. Studies have reported that the threshold dose should be 12-14 Gy in a single fraction for reliable control by X-rays in a postoperative setting, and that radiotherapy should be given immediately after excision [7,[17][18][19]. Enhamre and Hammar [7] observed no association between treatment outcomes and the time interval between excision and radiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, early intervention with radiotherapy should be the best timing for the treatment of keloids. Studies have reported that the threshold dose should be 12-14 Gy in a single fraction for reliable control by X-rays in a postoperative setting, and that radiotherapy should be given immediately after excision [7,[17][18][19]. Enhamre and Hammar [7] observed no association between treatment outcomes and the time interval between excision and radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the threshold dose should be 12-14 Gy in a single fraction for reliable control by X-rays in a postoperative setting, and that radiotherapy should be given immediately after excision [7,[17][18][19]. Enhamre and Hammar [7] observed no association between treatment outcomes and the time interval between excision and radiation. Sakamoto et al [20] stated that the time interval from operation did not affect the local control and adverse effects after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7) Low dose external radiation is currently used for a number of different problems including the prevention of keloid formation after surgery and recurrence of pterygium after surgical removal. [8][9][10][11] Restenosis may be considered as a type of exuberant wound healing. The formation of new intraluminal tissue and the subsequent overall vessel constriction are similar to scar formation and contraction that occurs during the healing process after injury.…”
mentioning
confidence: 99%
“…Histopathological evidence as revealed by autopsy studies shows the responses of human coronary arteries to angioplasty are a form of vessel wall stretch and dissection injury with subsequent scarring in the form of a proliferative neointima rich in extracellular matrix, similar to scars in other tissues. [12][13][14][15][16] This safe and effective use of radiation therapy for benign proliferative conditions has led a number of investigators to test whether local irra-diation might affect restenosis. This review is focused on the potential clinical application of endovascular brachytherapy for restenosis prevention.…”
mentioning
confidence: 99%